Students’ Speaking Ability Awareness: A Qualitative Study at Zawiyah English Club Iain Langsa - Julfikar Nurdin (JADEs Journal of Academia in English Education, 2021)
The aim of this research is to analyze how the speaking class at Zawiyah English Club can improve the students’ speaking ability awareness. In conducting the study, this study used qualitative method with phenomenology approach. The total number of samples is 10 students who joined in Zawiyah English Club IAIN Langsa. The procedure of the collecting data or instrument used in this study with interviewed and observation method. The results of this research were successful in analyzing how the speaking class at Zawiyah English Club can improve the students’ speaking ability awareness. Conducting a monastic class program held in every Thursday regularly and when they are doing activities together, they keep trying to use English and everyone in the environment motivates each other. They feel aware to speak English and they always improve their skills eah other. They feel when they study, they are not under pressure. They also tend to prefer practicing speaking in the speaking classes held at Zawiyah English Club than regular classes in lectures. Then, all of the students stated that they believe they can improve their speaking ability because Zawiyah English Club could increase their awareness and confidence in speaking.